Loving nature: past, present, and future - Rolston, Holmes, 1932-2025, author; Sage, publisher (Colorado State University. Libraries, 2016)
At this hinge point in planetary history, the future of Earth is in our hands. How ought Christians to love nature? In the biblical past, Earth was a miracle, a divine gift. Today, the land of promise is a vision of a planet with promise. Ancient certainty needs to become an urgent future hope.
Keywords: nature; promised land; garden Earth; creation; wilderness; communities; environmental ethics; Earth